A hybrid DTC-DSC drive for high performance induction motor control - Jidin, Auzani; Nik Idris, Nik Rumzi; Mohamed Yatim, Abdul Halim; Sutikno, Tole (Korean Institute of Power Electronics, 2011)
This paper describes a hybrid induction motor drive system incorporating DTC-hysteresis and Direct Self Control (DSC) schemes to achieve excellent dynamic performance. The control scheme is switched from a circular to a hexagonal flux locus whenever a dynamic condition is encountered. On the other hand, when the motor operates under steady state conditions, a circular flux locus is used. Without major modifications to the simple structure of a basic DTC, hexagonal flux locus operation is established by modifying the flux error status, before it is fed to the look-up table. The feasibility of the proposed hybrid scheme to achieve excellent control performance is verified by experimental results.